Synthesis of 3-Chloro-1-(2-chloro-1,8-naphthyridin-7-yl)-4- arylazetidin-2-ones and 3-(2-Chloro-1,8-naphthyridine-7-yl)-2- arylthiazolidin-4-ones From 2-Amino-7-chloro-1,8-naphthyridine - CHARY MARINGANTI, THIRUMALA; EPPAKAYALA, LAXMINARAYANA; ATMAKURI, NARENDER; SHANKAR SRIPELLY, SHIVA (Asian Journal of Chemistry, 2010)
2-Amino-7-chloro-1,8-napthyridine (1) undergoes condensation with different aromatic aldehydes to form 2-arylideneamino-7-chloro- 1,8-naphthyridines (2-6). These imines when treated with different reagents varied substituted derivatives are produced. Compounds 2-6 are converted to different dyes (7-11) by diazotization. Azetidinones (12-16) are obtained by the reaction of 2-6 and chloroacetylchloride in presence of triethylamine. Finally the imines are converted to thiazolidinones (17-21) by treating compounds with thioglycolic acid.